Algebra I : 1001 practical problems - Sterling, Mary Jane. (b, 2022)
Algebra I: 1001 Practice Problems for Dummies gives you more than a thousand chances to build your algebra know-how. This workbook is full of practice problems covering every topic in your Algebra I course. Basic operations, algebraic properties, polynomials, quadratic equation, graphing -- it's all here. Pencil your way through the book or get online to track your progress and build customized problem sets. Then, follow along with step-by-step explanation with every solution.
Chapter 1. Signing on with Signed Numbers.--Chapter 2. Recognizing Algebraic Properties and Notations.--Chapter 3. Working with Fractions and Decimals.--Chapter 4. Making exponential expressions and operations more compatible.--Chapter 5. Raking radicals.--Chapter 6. Creating more user-friendly algebraic expressions.--Chapter 7. Multiplying by one or more terms.--Chapter 8. Dividing algebraic expressions.--Chapter 9. Factoring basics.--Chapter 10. Factoring binomials.--Chapter 11. Factoring quadratic trinomials.--Chapter 12. Other factoring techniques.--Chapter 13. Solving linear equations.--Chapter 14. Taking on quadratic equations.--Chapter 15. Solving polynomials with powers three and higher.--Chapter 16. Reining in radical and absolute value equations.--Chapter 17. Making inequalities more fair.--Chapter 18. Using established formulas.--Chapter 19. Using formulas in geometric story problems.--Chapter 20. Tackling traditional story problems.--Chapter 21. Graphic basics.--Chapter 22. Using the algebra of lines.--Chapter 23. Other graphing topics.--Part 2. The answers.--Chapter 24. The answers.
Includes index.
Keywords: ALGEBRA; ALGEBRA PROBLEMS, EXERCISES, ETC; ALGEBRA; EXERCISE BOOKS; ALGEBRA AND TRIGONOMETRY